Vrikka Vikara Chikitsa: A Case Study Of Ayurvedic Approach In Managing Ckd With A History Of Prameha And Hridroga (Prakriti - The International Multidisciplinary Research Journal, 2025)
Chronic kidney disease (CKD) is a progressive condition characterized by  declining kidney function, often coexisting with hypertension, type 2 diabetes  mellitus (T2DM), and coronary artery disease (CAD), amplifying cardiovascular  risks. Vrikka Vikar often manifests as a result of Prameha and Raktagata Vata,  which collectively aggravate Hridroga, forming a complex pathophysiological  interplay requiring a holistic Ayurvedic approach involving Shodhana and Shamana therapies. This case report presents a 52-year-old male with CKD, hypertension,  T2DM, and CAD who underwent Ayurvedic interventions alongside conventional  treatments at Jeena Sikho Lifecare Limited Hospital, Derabassi, Punjab, India. The  patient experienced symptoms such as weakness, fatigue, frothy urine, disturbed  sleep, and lower back pain. Following a 13-day inpatient Ayurvedic treatment  regimen, the patient’s symptoms improved significantly. Laboratory investigations  revealed a reduction in serum urea from 137.17 mg/dL to 75.44 mg/dL, serum  creatinine from 6.88 mg/dL to 5.58 mg/dL, and uric acid from 7.30 mg/dL to  6.44 mg/dL. These outcomes suggest that Ayurvedic interventions may support  improved kidney function and overall well-being. Further controlled studies are  recommended to validate these findings and develop standardized treatment  protocols.
Keywords: Ayurveda; Chronic Kidney Disease (CKD); Hridroga; Hypertension; Madhumeha; Panchakarma; Vataj pandu; Vrikka Vikar